OP0091 A Retrospective Look at the Recurrence of Digital Ulcers in Patients with Scleroderma after Discontinuation of Oral Treprostinil. (10th June 2014) - Shah, A.A.; Schiopu, E.; Chatterjee, S.; Csuka, M.E.; Frech, T.; Goldberg, A.; Spiera, R.; Peng, S.L.; Steen, V.
Abstract : Background: Ischemic digital ulcers (DU) are a frequent complication in systemic sclerosis, estimated to occur in over 40% of patients. Treprostinil diethanolamine, a newer prostacyclin analog that has been developed for oral delivery, improves cutaneous perfusion and temperature in scleroderma patients. A large randomized, double-blind, placebo-controlled clinical trial of treprostinil diethanolamine was conducted in scleroderma patients with DU (ClinicalTrials.gov identifier NCT00775463 ). While this trial did not meet the desired endpoint (change in net ulcer burden at 20 wks), there was a significant improvement in several secondary endpoints that measured Raynaud's severity. Subjects enrolled into an open label extension study (DISTOL-EXT) after the clinical trial, and after termination of DISTOL-EXT, all participants were withdrawn from oral treprostinil. Objectives: We investigated whether active, indeterminate, and total ulcer burden increased in DISTOL-EXT participants after they discontinued oral treprostinil. Methods: In this multi-center, retrospective study, medical records for the year after discontinuation of treprostinil were reviewed. Data from these routine clinical visits were abstracted into a template designed a priori to capture information on the number of active and indeterminate DU at the end of the extension study and at subsequent visits. Participants who did not have a subsequent visit with documentation of DU status were excluded from this study. We examined the number of new DU that developed from the end of the extension study (baseline) through the first year after discontinuation of treprostinil. The number of active, indeterminate and total DU 3-6 months (time A) and >6-12 months (time B) after discontinuation of treprostinil were compared to baseline by the paired t-test. Results: Fifty-one subjects from 9 SSc Centers were included for analysis. At the conclusion of the treprostinil extension study, the mean number of active, indeterminate and total DU was 0.25 (SD 0.63), 0.22 (SD 0.54) and 0.47 (SD 0.78), respectively. The number of active DU increased from baseline to time A (mean 1.62, p=0.004, N=23) and time B (mean 1.03, p=0.076, N=30). The number of indeterminate DU increased from baseline to time B (mean 0.42, p=0.03, N=30) but not time A. The total DU burden increased significantly from baseline to time A (mean 2.1, p=0.002, N=23) and time B (mean 1.45, p=0.01, N=30) as shown in the Figure. The majority of patients required intensive vasodilator therapy and pain medication: calcium channel blockers (60.8%), PDE 5 inhibitors (21.6%), any pain medication (58.8%), opioids (33.3%). Three patients were hospitalized for complications from digital ulcers, and four patients required surgical intervention. Five patients were subsequently diagnosed with pulmonary hypertension. Conclusions: Total DU burden increased significantly after discontinuation of oral treprostinil diethanolamine. These data provide supportive evidence of a beneficial effect of oral treprostinil diethanolamine for the vascular complications of SSc. Disclosure of Interest: A. Shah Grant/research support: United Therapeutics, E. Schiopu Grant/research support: United Therapeutics, Actelion, MedImmune, Celgene, Speakers bureau: Previously on United Therapeutics Speakers bureau, S. Chatterjee Grant/research support: United Therapeutics, M. E. Csuka Grant/research support: United Therapeutics, T. Frech Grant/research support: United Therapeutics, A. Goldberg Grant/research support: United Therapeutics, R. Spiera Grant/research support: United Therapeutics, S. Peng Grant/research support: United Therapeutics, V. Steen Grant/research support: United Therapeutics DOI: 10.1136/annrheumdis-2014-eular.2257